Field Day 2006 forage research supplement - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
This publication is a supplement to Field Day 2006, Southwest Research-Extension Center Report of Progress SRP 961 from the Kansas Agricultural Experiment Station.
Keywords: Kansas; Hard red winter wheat; Hard white winter wheat; Cool-season grass; Warm-season grass; Corn harvest residue; Yield